Development of Innovative Products Based on Local Wisdom to Increase the Competitiveness of MSMEs - Galstyan, Levon; Hakobyan, Aram; Guliyeva, Leyla (Journal of Loomingulisus ja Innovatsioon, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the economic development of many countries, including Indonesia. However, MSMEs often face challenges in enhancing competitiveness, especially in the global market. One potential solution lies in the development of innovative products based on local wisdom, which can add unique value and appeal. This study aims to explore how MSMEs can develop innovative products based on local wisdom to enhance their competitiveness. Specifically, it investigates the integration of local cultural values, traditional knowledge, and sustainable practices into product design and development processes within MSMEs. This research employs a qualitative case study approach, focusing on several MSMEs in Indonesia that have successfully incorporated local wisdom into their product offerings. Data was collected through interviews with business owners, product designers, and local community members, along with field observations. The study also analyzed secondary data from industry reports and market trends. The findings indicate that MSMEs that integrate local wisdom into their products can significantly improve their market differentiation and appeal. The study identifies key factors such as cultural authenticity, sustainable sourcing, and the ability to tell a compelling product story as essential to enhancing competitiveness.